Evaluasi Usability Pada Aplikasi Learn C++ Menggunakan Metode Usabilty Testing Studi Kasus SMKN 3 Malang - Dimas Anugerah Asprila; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The android application is one of the supporters of today's digital education applications. According to the results of direct interviews conducted by researchers with one of the Computer Network Engineering teachers at SMKN 3 Malang, it can be concluded that the lack of computer learning media facilities and the limited number of students who have laptops are a problem when the teacher teaches basic programming lessons. To solve problems when the learning process takes place Learn C ++ is a solution application from the teacher, to learn programming and writing code. The purpose of this study was to determine the level of usability Learn C ++ and make recommendations for improvements from the user. The method used is Usability testing using the System Usability Scale (SUS) questionnaire. Based on the research conducted, it was found 7 problems, and provided 7 recommendations for improvement solutions, the conclusions obtained increase the parameter values ​​of efficiency, effectiveness, and satisfaction. Where on the old interface the effectiveness rate was 90.4%, then on the new interface it increased to 100%. The efficiency level of the mean number of touch value in the first evaluation got a value of 3.7 while in the second evaluation it got a value of 3.02, therefore, it can be seen that there is a decrease of 0.68 which means that the recommendation for interface improvements given gives better application efficiency. The satisfaction obtained through the first evaluation received a value of 67%, while the second evaluation received a value of 76%. Experienced an increase in value of 18%, which means that respondents are more satisfied with the recommendations for interface improvements given.